Selection and Validation of Novel RT-qPCR Reference Genes under Hormonal Stimuli and in Different Tissues of Santalum album. Issue 1 (December 2018) - Yan, Haifeng; Zhang, Yueya; Xiong, Yuping; Chen, Qingwei; Liang, Hanzhi; Niu, Meiyun; Guo, Beiyi; Li, Mingzhi; Zhang, Xinhua; Li, Yuan; Teixeira da Silva, Jaime; Ma, Guohua
Abstract Reverse transcription quantitative real-time polymerase chain reaction (RT-qPCR) is a widely used technique to investigate gene expression levels due to its high throughput, specificity, and sensitivity. An appropriate reference gene is essential for RT-qPCR analysis to obtain accurate and reliable results. To date, no reliable reference gene has been validated for the economically tropical tree, sandalwood (Santalum album L.). In this study, 13 candidate reference genes, including 12 novel putative reference genes selected from a large set ofS .album transcriptome data, as well as the currently used β-actin gene (ACT ), were validated in different tissues (stem, leaf, root and callus), as well as callus tissue under salicylic acid (SA), jasmonic acid methyl ester (MeJA), and gibberellin (GA) treatments using geNorm, NormFinder, BestKeeper, Delta Ct and comprehensive RefFinder algorithms. Several novel candidate reference genes were much more stable than the currently used traditional geneACT .ODD paired withFbp1 for SA treatment, CSA andFbp3 for MeJA treatment, PP2C andFbp2 for GA treatment, as well asFbp1 combined withFbp2 for the total of three hormone treatments were the most accurate reference genes, respectively.FAB1A, when combined withPP2C, was identified as the most suitable reference gene combination for the four tissues tested, while the combination ofHLMt, PPR andFAB1A were the most optimal reference genes for all of the experimental samples. In addition, to verify our results, the relative expression level of theSaSSy gene was evaluated by the validated reference genes and their combinations in the threeS .album tissues and under MeJA treatment. The evaluated reference genes in this study will improve the accuracy of RT-qPCR analysis and will benefitS .album functional genomics studies in different tissues and under hormone stimuli in the future.